Red‐emitting distributed‐feedback ridge‐waveguide laser based on high‐order surface grating. Issue 9 (1st May 2018) - Fricke, J.; Brox, O.; Wenzel, H.; Matalla, M.; Ressel, P.; Knigge, A.
Abstract : Distributed‐feedback ridge‐waveguide lasers emitting around 670 nm have been fabricated and experimentally characterised. Wavelength stabilisation is provided by 40th Bragg order surface gratings dry‐etched into the p‐GaAs–AlGaAs–AlGaInP layer structure. The large grating period of 4.2 µm allows the injection of the current between the grooves of the grating without sacrificing the electrical and optical properties noticeably. The 1.5 mm long devices achieve an output power of 50 mW at an injection current of 180 mA. The side mode suppression ratio is 50 dB at 150 mA.